Preparation method of rare earth element-based liquid nanoparticles, photoresist composition and 3D pattern

By synthesizing rare earth element-based liquid nanoparticles in photoresist, the pattern quality problem caused by the large particles of rare earth elements in photoresist matrix and solid compound are solved, and efficient doping of rare earth elements and improving the pattern structure quality is achieved.

CN119841850APending Publication Date: 2025-04-18YONGJIANG LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510048130.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, rare earth elements are difficult to dissolve in the photoresist matrix, which limits the high content and high efficiency doping of rare earth elements, and the solid compound particles are large, resulting in particle agglomeration, light scattering and heat accumulation problems in the two-photon patterning technology, which damages the pattern quality.

Method used

Rare earth metal acetate is used to react with organic acid ligand and organic amine ligand in an organic dispersion solvent to form liquid nanoparticles. By heating and evaporating the organic dispersion solvent, rare earth element-based liquid nanoparticles are obtained. These nanoparticles have good miscibility with the photoresist matrix and maintain extremely small particle size.

Benefits of technology

The efficient doping of rare earth elements is achieved, the problem of rare earth elements being difficult to dissolve in photoresist matrix is ​​solved, and the pattern quality problems caused by solid compounds in two-photon patterning technology are avoided, which significantly improves the structural quality of the pattern.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841850A_ABST
    Figure CN119841850A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of rare earth element-based liquid nanoparticles, a photoresist composition and a 3D pattern. The preparation method comprises the following steps: dissolving rare earth metal acetate in an organic dispersion solvent, dropwise adding an organic acid ligand under the protection of nitrogen to react with an organic amine ligand to obtain liquid nanoparticles dissolved in the organic dispersion solvent, and heating to evaporate the organic dispersion solvent to obtain rare earth element-based liquid nanoparticles which are small in particle size and good in miscibility with a photoresist matrix. And after mixing, the extremely small particle size can still be kept, and the pattern obtained through two-photon 3D manufacturing has good structural quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanoparticles and photolithography, and in particular relates to a preparation method of rare earth element-based liquid nanoparticles, a photoresist composition and a 3D pattern. Background Art

[0002] Doping rare earth elements into photoresists is a common method for two-photon 3D manufacturing of functional devices. Generally, rare earth elements have very low solubility when dissolved in organic resins by heating, ultrasound, etc. However, the effective rare earth doping concentration in micro-nano devices is often the key to the high efficiency of various functions (such as photoluminescence, laser gain, etc.).

[0003] In recent years, organic-inorganic hybrid photoresists have become increasingly important in the ever-advancing Moore's Law due to their excellent properties such as high resolution, low roughness and high corrosion resistance. The small size and uniform distribution of hybrid photoresist nanoparticles (such as methacrylate zirconium oxide nanoparticles and organic tin complexes, etc.) naturally meet the needs of two-photon patterning, avoiding the problems of light scattering and heat accumulation caused by fillers in organic resins. However, their solid form is still difficult to dissolve in commonly used resin materials, limiting the micro-nano manufacturing capabilities of two-photon. Summary of the invention

[0004] In view of the above-mentioned technical status quo, the present invention provides a method for preparing rare earth element-based liquid nanoparticles. The rare earth element-based nanoparticles prepared by this method are in liquid state and have a small particle size. They have good miscibility with conventional photoresist matrices and can still maintain an extremely small particle size after mixing. They have good application prospects in two-photon patterning.

[0005] The technical solution provided by the present invention is: a method for preparing rare earth element-based liquid nanoparticles, comprising the following steps:

[0006] Rare earth metal acetate is dissolved in an organic dispersion solvent, and an organic acid ligand and an organic amine ligand are dropped under the protection of nitrogen or an inert gas to react to obtain liquid nanoparticles dissolved in the organic dispersion solvent, and the organic dispersion solvent is heated and evaporated to obtain rare earth element-based liquid nanoparticles.

[0007] In actual synthesis, if there is precipitation in the reaction system after the reaction, centrifugation is first performed, and the upper clear solution is taken after centrifugation, and the organic dispersing solvent therein is heated and evaporated to obtain rare earth element-based liquid nanoparticles. Preferably, the speed of the centrifugal operation is selected from 6000 rpm to 10000 rpm.

[0008] The particle size of the rare earth element-based liquid nanoparticles is in the range of 0.8nm-8nm, especially between 0.8nm-2nm.

[0009] Preferably, the solution after the reaction is first filtered, and then heated to evaporate the organic dispersing solvent therein. More preferably, the solution is filtered through a filter with a pore size of 0.1 um to 0.5 um.

[0010] As a preferred implementation method, the organic acid ligand and the organic amine ligand are dispersed in the organic dispersion solvent to obtain a dispersion solution; the rare earth metal acetate is dissolved in the organic dispersion solvent and slowly dripped into the dispersion solution under nitrogen protection.

[0011] The rare earth metal acetate is not limited and can be selected from one or more of erbium acetate, ytterbium acetate, praseodymium acetate, neodymium acetate, yttrium acetate, thulium acetate, holmium acetate, samarium acetate, cerium acetate and the like.

[0012] The organic dispersing solvent is not limited and can be selected from one or more of ethyl acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, methanol, ethanol, and propanol.

[0013] The organic acid ligand is not limited and can be selected from aromatic carboxylic acids, and its general formula is HOOC-R1-C 6 H 4 -R2, wherein R1 can be selected from but not limited to C0-C3 alkyl, R2 can be selected from but not limited to one or more of halogen, carboxyl, carbonyl, hydroxyl, amino, C1-C10 alkyl, C2-C10 alkenyl, C3-C10 aryl, benzophenone derivatives, and thioxanthone derivatives.

[0014] The organic amine ligand may be selected from, but not limited to, chain amines and their derivatives or cyclic amines and their derivatives. Chain amines and their derivatives may be selected from, but not limited to, one or more of trimethylamine, triethylamine, tripropylamine, tripentylamine, triisopropylamine, diethylamine, dimethylamine, etc.; cyclic amines and their derivatives may be selected from, but not limited to, one or more of imidazole and its derivatives, pyridine and its derivatives, piperidine and its derivatives, pyrimidine and its derivatives, pyrrole and its derivatives, etc.

[0015] The molar mass ratio of the rare earth metal acetate, the organic acid ligand and the organic amine ligand can be selected from 1:(0.5-3):(0.5-3).

[0016] Preferably, the reaction is carried out at 60°C-80°C.

[0017] Preferably, the reaction time is 18 hours to 24 hours.

[0018] The evaporation method is not limited, such as rotary evaporation, etc. Preferably, the evaporation temperature is 20°C-40°C.

[0019] Compared with the prior art, the present invention utilizes ligand chemistry to add organic acid ligands and organic amine ligands to a rare earth metal acetate solution, wherein the organic acid ligand replaces the acetate group of the rare earth metal acetate, and the organic amine ligand shields the charge of the rare earth metal core, thereby reducing the interaction force between particles and obtaining rare earth element-based nanoparticles with liquid behavior.

[0020] In the prior art, rare earth elements are often added to photoresist compositions in the form of solid compounds, which has the problem that rare earth elements are difficult to dissolve in the photoresist matrix, thereby failing to meet the high-content and efficient doping requirements of rare earth elements; and the solid compound particles are relatively large, and still maintain a relatively large particle size under vigorous stirring, which will cause particle agglomeration, light scattering and heat accumulation problems in two-photon patterning technology, thereby damaging the pattern quality. The rare earth element-based liquid nanoparticles synthesized by the method of the present invention have good miscibility with the conventional matrix of the photoresist, and can still maintain a very small particle size after mixing, which solves the problem that rare earth elements are difficult to dissolve in the photoresist matrix and realizes efficient doping of rare earth elements on the one hand, and solves the problem that the large particles of the rare earth element compound cause particle agglomeration, light scattering and heat accumulation in the two-photon patterning technology, thereby damaging the pattern quality.

[0021] The present invention also provides a photoresist composition, comprising an organic resin, a photoinitiator and rare earth element-based liquid nanoparticles synthesized by the method of the present invention, wherein the rare earth element-based liquid nanoparticles are uniformly dispersed in the organic resin. The pattern obtained by two-photon 3D manufacturing using the photoresist composition has good structural quality.

[0022] The organic resin is not limited and can be selected from acrylate and its derivatives. The acrylate and its derivatives are not limited and can be selected from one or more of pentaerythritol tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, polydipentaerythritol pentaacrylate, and 3-(trimethoxymethylsilyl)propyl methacrylate.

[0023] The mass ratio of the rare earth element-based liquid nanoparticles to the organic resin is determined according to actual needs and can be selected from (0.1-1):1.

[0024] Preferably, the rare earth element-based liquid nanoparticles are mixed with an organic resin and stirred by magnetic force at a certain temperature for a certain period of time.

[0025] The photoinitiator can be selected from but not limited to one or more of 2-isopropylthioxanthone, benzophenone, 2,4-diethylthioxanthone, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone. Preferably, the mass proportion of the photoinitiator in the composition can be selected from 0-0.05.

[0026] Preferably, two-photon patterning is performed using the photoresist composition to obtain a 3D pattern, as follows:

[0027] The photoresist composition is placed on the surface of a substrate, and patterning is performed by two-photon polymerization femtosecond laser direct writing. After completion, the substrate is taken out and immersed in a developer for development, and the pattern is obtained after drying.

[0028] The substrate is not limited and can be selected from polished silicon wafers, quartz wafers, sapphire wafers, and the like.

[0029] The developer is not limited and can be selected from one or more of isopropyl alcohol, toluene, o-xylene, 4-methyl-2-pentanol, propylene glycol monomethyl ether acetate, ethyl acetate and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 These are pictures of rare earth-based liquid nanoparticle samples synthesized in Examples 1, 2, 3, 4, 5, 6, and 7.

[0031] Figure 2 The particle size distribution of the rare earth-based liquid nanoparticles synthesized in Examples 1, 2, 3, 4, 5, 6, and 7 is obtained by testing with a dynamic light scattering instrument.

[0032] Figure 3 This is a heating-cooling curve of the erbium-based liquid nanoparticle Er-VBA synthesized in Example 1 obtained by differential scanning calorimetry testing.

[0033] Figure 4 This is the appearance of the mixed solution Er-VBA-PETA in Example 1-1.

[0034] Figure 5 This is an appearance diagram of the mixture of erbium acetate and pentaerythritol triacrylate in Example 1-1.

[0035] Figure 6 It is a particle size distribution diagram obtained by testing the photoresist compositions in Examples 1-1, 2-1, 3-1, 4-1, 5-1, 6-1, and 7-1 using a dynamic light scattering instrument.

[0036] Figure 7 It is a two-photon exposure structure of the photoresist composition containing erbium-based liquid nanoparticles Er-VBA in Example 1-2.

[0037] Figure 8 is a microscope picture of the photoresist composition containing erbium acetate in Comparative Example 1-2-1.

[0038] Fig. 9 This is the two-photon exposure structure of the photoresist composition without adding metal-based nanoparticles in Comparative Example 1-2-2.

[0039] Fig.10 This is the heating-cooling curve of the yttrium-based liquid nanoparticle Y-VBA synthesized in Example 2 obtained by differential scanning calorimetry testing.

[0040] Fig.11 This is the appearance diagram of the mixed solution Y-VBA-PETA in Example 2-1.

[0041] Fig.12 This is an appearance diagram of the mixture of yttrium acetate and pentaerythritol triacrylate in Example 2-1.

[0042] Fig.13 It is a two-photon exposure structure of the photoresist composition containing yttrium-based liquid nanoparticles Y-VBA in Example 2-2.

[0043] Fig.14 is a microscope picture of the photoresist composition containing yttrium acetate in Comparative Example 2-2-1.

[0044] Fig.15 This is the heating-cooling curve of the neodymium-based liquid nanoparticles Nd-VBA synthesized in Example 3 obtained by differential scanning calorimetry testing.

[0045] Fig.16 This is the appearance of the mixed solution Nd-VBA-PETA in Example 3-1.

[0046] Fig.17 This is the appearance of the mixture of neodymium acetate and pentaerythritol triacrylate in Example 3-1.

[0047] Fig.18 It is a two-photon exposure structure of the photoresist composition containing neodymium-based liquid nanoparticles Nd-VBA in Example 3-2.

[0048] Fig.19 is a microscope picture of the photoresist composition containing neodymium acetate in Comparative Example 3-2-1.

[0049] Fig. 20 This is the appearance of the mixed solution Pr-VBA-PETA in Example 4-1.

[0050] Fig.21 This is the appearance of a mixture of praseodymium acetate and pentaerythritol triacrylate.

[0051] Fig. 22 This is the appearance picture of the mixed solution Ho-VBA-PETA in Example 5-1.

[0052] Fig.23 This is the appearance of a mixture of holmium acetate and pentaerythritol triacrylate.

[0053] Fig.24This is the appearance of the mixed solution Tm-VBA-PETA in Example 6-1.

[0054] Fig.25 This is the appearance of a mixture of thulium acetate and pentaerythritol triacrylate.

[0055] Fig.26 This is the appearance of the mixed solution Yb-VBA-PETA in Example 7-1.

[0056] Fig. 27 This is the appearance of a mixture of ytterbium acetate and pentaerythritol triacrylate. DETAILED DESCRIPTION

[0057] The present invention is further described in detail below in conjunction with embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention, and non-essential improvements and adjustments made to the present invention by those skilled in the art based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0058] The words “include”, “including” and the like used in the present invention should be interpreted as including rather than being exclusive or exhaustive; that is, the meaning is “including but not limited to”.

[0059] Embodiment 1:

[0060] Take 1g of erbium acetate and dissolve it in 4mL of ethyl acetate. Slowly add 4mL of ethyl acetate mixed solution of 1.12g of vinylbenzoic acid and 0.4g of diethylamine under nitrogen protection, and stir at 65°C for 24 hours to obtain a clear solution. After filtering the solution through a 0.22um needle filter, vacuum rotary evaporation is performed at 30°C to obtain erbium-vinylbenzoic acid (referred to as Er-VBA) nanoparticles.

[0061] The appearance of the erbium-based nanoparticles Er-VBA is shown in the attached Figure 1 As shown, it is in liquid form.

[0062] The particle size distribution of the erbium-based liquid nanoparticles Er-VBA obtained by dynamic light scattering is as follows: Figure 2 As shown, the particle size is mainly concentrated in the range of 1.0nm-2.0nm.

[0063] The heating-cooling curve of the erbium-based liquid nanoparticle Er-VBA obtained by differential scanning calorimetry is as follows: Figure 3 As shown, it is shown that the nanoparticle Er-VBA liquefies at -38.24°C, so the nanoparticle is in liquid at room temperature.

[0064] Example 1-1:

[0065] 0.9 g of the erbium-based liquid nanoparticles Er-VBA prepared in Example 1 and 2.1 g of pentaerythritol triacrylate were mixed and stirred to obtain a mixed liquid referred to as Er-VBA-PETA.

[0066] The appearance of the mixed solution Er-VBA-PETA is as follows Figure 4 As shown, it is shown that the erbium-based liquid nanoparticles Er-VBA have good solubility in pentaerythritol triacrylate.

[0067] As a comparison, 0.9 g of erbium acetate and 2.1 g of pentaerythritol triacrylate were mixed to obtain a mixed solution denoted as Er-PETA. Figure 5 As shown, it is shown that the solubility of erbium acetate in pentaerythritol triacrylate is low. Figure 4 and Figure 5 , it can be seen that compared with erbium acetate, the solubility of erbium-based liquid nanoparticles Er-VBA in pentaerythritol triacrylate is greatly improved.

[0068] The particle size distribution of the mixed solution Er-VBA-PETA obtained by dynamic light scattering is as follows Figure 6 As shown, its particle size is mainly concentrated in the range of 1.0nm-2.0nm. Figure 2 and Figure 6 It can be seen that the erbium-based liquid nanoparticles Er-VBA still maintain a very small particle size after mixing with pentaerythritol triacrylate.

[0069] Embodiment 1-2:

[0070] 0.9 g of erbium-based liquid nanoparticles Er-VBA, 2.1 g of pentaerythritol triacrylate and 0.03 g of photoinitiator prepared in Example 1 were mixed and stirred for 4 hours and used as a photoresist composition for two-photon patterning. The photoinitiator was composed of 2-isopropylthioxanthone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone and 4-dimethylamino-ethyl benzoate in a mass ratio of 1:1:1, hereinafter referred to as I3E.

[0071] The two-photon patterning method is as follows:

[0072] The photoresist composition is dropped onto the surface of the substrate, a laser with a wavelength of 515 nm is focused on the plane where the photoresist and the substrate are in contact, and the stage is moved downward with high precision according to the program, and patterning is performed in the photoresist in this step; after the patterning is completed, the substrate is taken out and completely immersed in a developer solution of propylene glycol monomethyl ether acetate for development for 5 minutes, and then dried with nitrogen to obtain the following Figure 7 Pattern shown.

[0073] Comparative Example 1-2-1:

[0074] 0.9 g of erbium acetate, 2.1 g of pentaerythritol triacrylate and 0.03 g of I3E photoinitiator were mixed and stirred for 4 hours to prepare a photoresist composition for two-photon patterning. The patterning method was the same as that in Example 1-2. Figure 8 As shown in the microscope image, the particles of the erbium acetate-doped photoresist are too large to be printed.

[0075] Comparative Example 1-2-2:

[0076] 3 g of pentaerythritol triacrylate and 0.03 g of I3E photoinitiator were mixed and stirred for 4 hours to form a photoresist composition for two-photon patterning. The patterning method was the same as that in Example 1-2. The obtained pattern was as follows: Fig. 9 shown.

[0077] contrast Figure 7 and Figure 8 , it can be seen that: compared with the photoresist composition doped with erbium acetate, the structural quality of the 3D pattern obtained by doping with erbium-based liquid nanoparticles Er-VBA is improved. The photoresist composition doped with erbium acetate cannot print structures in the femtosecond laser direct writing system due to problems such as large particles. In contrast, the photoresist composition doped with erbium-based liquid nanoparticles Er-VBA can run in the femtosecond laser direct writing system and print high-quality structures.

[0078] contrast Figure 7 and Fig. 9 It can be seen that the printing integrity and structural quality of the photoresist composition doped with liquid erbium-based liquid nanoparticles Er-VBA are no different from those of conventional resin materials, which indirectly proves that this type of rare earth-based liquid nanoparticles can achieve effective doping with a high mass fraction.

[0079] Embodiment 2:

[0080] Take 1g of yttrium acetate and dissolve it in 4mL of ethyl acetate. Slowly add 4mL of ethyl acetate mixed solution of 1.12g of vinylbenzoic acid and 0.4g of diethylamine under nitrogen protection, and stir at 65°C for 24 hours to obtain a clear solution. After filtering the solution through a 0.22um needle filter, vacuum rotary evaporation is performed at 30°C to obtain yttrium-vinylbenzoic acid (denoted as Y-VBA) nanoparticles.

[0081] The appearance of the yttrium-based nanoparticles Y-VBA is shown in the attached Figure 1 As shown, it is in liquid form.

[0082] The particle size distribution of the yttrium-based liquid nanoparticles Y-VBA obtained by dynamic light scattering is as follows Figure 2 As shown, the particle size is mainly concentrated in the range of 1.0nm-2.0nm.

[0083] The heating-cooling curve of the yttrium-based liquid nanoparticle Y-VBA obtained by differential scanning calorimetry Fig.10 As shown, it is shown that the nanoparticle Y-VBA liquefies at -47.27°C under the heating curve, so the nanoparticle is liquid at room temperature.

[0084] Example 2-1:

[0085] 0.9 g of the yttrium-based liquid nanoparticles Y-VBA prepared in Example 2 and 2.1 g of pentaerythritol triacrylate were mixed and stirred to obtain a mixed liquid referred to as Y-VBA-PETA.

[0086] The appearance of the mixed solution Y-VBA-PETA is as follows Fig.11 As shown, it is shown that the yttrium-based liquid nanoparticles Y-VBA have good solubility in pentaerythritol triacrylate.

[0087] As a comparison, 0.9 g of yttrium acetate and 2.1 g of pentaerythritol triacrylate were mixed to obtain a mixed solution denoted as Y-PETA. Fig.12 As shown, it is shown that the solubility of yttrium acetate in pentaerythritol triacrylate is low. Fig.11 and Fig.12 , it can be seen that compared with yttrium acetate, the solubility of yttrium-based liquid nanoparticles Y-VBA in pentaerythritol triacrylate is greatly improved.

[0088] The particle size distribution of the mixed solution Y-VBA-PETA obtained by dynamic light scattering is as follows Figure 6 As shown, its particle size is mainly concentrated in the range of 1.0nm-2.0nm. Figure 2 and Figure 6 , it can be seen that the yttrium-based liquid nanoparticles Y-VBA still maintain a very small particle size after being mixed with pentaerythritol triacrylate.

[0089] Example 2-2:

[0090] 0.9 g of yttrium-based liquid nanoparticles Y-VBA, 2.1 g of pentaerythritol triacrylate and 0.03 g of I3E photoinitiator prepared in Example 2 were mixed and stirred for 4 hours to form a photoresist composition for two-photon patterning. The patterning method was the same as that in Example 1-2 to obtain the following: Fig.13 Pattern shown.

[0091] Comparative Example 2-2-1:

[0092] 0.9 g of yttrium acetate, 2.1 g of pentaerythritol triacrylate and 0.03 g of I3E photoinitiator were mixed and stirred for 4 hours to prepare a photoresist composition for two-photon patterning. Fig.14As shown in the microscope image, the particles of the yttrium acetate-doped photoresist are too large to be printed.

[0093] Embodiment 3:

[0094] Take 1g of neodymium acetate and dissolve it in 4mL of ethyl acetate. Slowly add 4mL of ethyl acetate mixed solution of 1.12g of vinylbenzoic acid and 0.4g of diethylamine under nitrogen protection, and stir at 65°C for 24 hours to obtain a clear solution. After filtering the solution through a 0.22um needle filter, vacuum rotary evaporation is performed at 30°C to obtain neodymium-vinylbenzoic acid (denoted as Nd-VBA) nanoparticles.

[0095] The appearance of the neodymium-based nanoparticles Nd-VBA is shown in the attached Figure 1 As shown, it is in liquid form.

[0096] The particle size distribution of the neodymium-based liquid nanoparticles Nd-VBA obtained by dynamic light scattering is as follows Figure 2 As shown, the particle size is mainly concentrated in the range of 1.0nm-2.0nm.

[0097] The heating-cooling curve of the neodymium-based liquid nanoparticle Nd-VBA obtained by differential scanning calorimetry is as follows Fig.15 As shown, it is shown that the nanoparticles Nd-VBA liquefies at -53.77°C under the heating curve, so the nanoparticles are liquid at room temperature.

[0098] Example 3-1:

[0099] 0.9 g of the neodymium-based liquid nanoparticles Nd-VBA prepared in Example 3 and 2.1 g of pentaerythritol triacrylate were mixed and stirred to obtain a mixed liquid referred to as Nd-VBA-PETA.

[0100] The appearance of the mixed solution Nd-VBA-PETA is as follows Fig.16 As shown, it is shown that the neodymium-based liquid nanoparticles Nd-VBA have good solubility in pentaerythritol triacrylate.

[0101] As a comparison, 0.9 g of neodymium acetate and 2.1 g of pentaerythritol triacrylate were mixed to obtain a mixed solution denoted as Nd-PETA. Fig.17 As shown, it is shown that neodymium acetate has low solubility in pentaerythritol triacrylate. Fig.16 and Fig.17 It can be seen that compared with neodymium acetate, the solubility of neodymium-based liquid nanoparticles Nd-VBA in pentaerythritol triacrylate is greatly improved.

[0102] The particle size distribution of the mixed solution Nd-VBA-PETA obtained by dynamic light scattering is as follows Figure 6As shown, its particle size is mainly concentrated in the range of 1.0nm-2.0nm. Figure 2 and Figure 6 It can be seen that the neodymium-based liquid nanoparticles Nd-VBA still maintain a very small particle size after mixing with pentaerythritol triacrylate.

[0103] Example 3-2:

[0104] The neodymium-based liquid nanoparticles Nd-VBA 0.9 g, pentaerythritol triacrylate 2.1 g and I3E photoinitiator 0.03 g prepared in Example 3 were mixed and stirred for 4 hours to form a photoresist composition for two-photon patterning. The patterning method was the same as that in Example 1-2 to obtain the following: Fig.18 Pattern shown.

[0105] Comparative Example 3-2-1:

[0106] 0.9 g of neodymium acetate, 2.1 g of pentaerythritol triacrylate and 0.03 g of I3E photoinitiator were mixed and stirred for 4 hours to prepare a photoresist composition for two-photon patterning. The patterning method was the same as that in Example 1-2. Fig.19 As shown in the microscope image, the particles of the neodymium acetate-doped photoresist are too large to be printed.

[0107] Embodiment 4:

[0108] Take 1g of praseodymium acetate and dissolve it in 4mL of ethyl acetate. Slowly add 4mL of ethyl acetate mixed solution of 1.12g of vinylbenzoic acid and 0.4g of diethylamine under nitrogen protection, and stir at 65°C for 24 hours to obtain a clear solution. After filtering the solution through a 0.22um needle filter, vacuum rotary evaporation is performed at 30°C to obtain praseodymium-vinylbenzoic acid (denoted as Pr-VBA) nanoparticles.

[0109] The appearance of the praseodymium-based nanoparticles Pr-VBA is shown in the attached figure. Figure 1 As shown, it is in liquid form.

[0110] The particle size distribution of the praseodymium-based liquid nanoparticles Pr-VBA obtained by dynamic light scattering is as follows Figure 2 As shown, the particle size is mainly concentrated in the range of 1.0nm-2.0nm.

[0111] The praseodymium-based liquid nanoparticle Pr-VBA is liquid at room temperature.

[0112] Example 4-1:

[0113] 0.9 g of the praseodymium-based liquid nanoparticles Pr-VBA prepared in Example 4 and 2.1 g of pentaerythritol triacrylate were mixed and stirred to obtain a mixed liquid referred to as Pr-VBA-PETA.

[0114] The appearance of the mixed solution Pr-VBA-PETA is as follows Fig. 20 As shown, the praseodymium-based liquid nanoparticles Pr-VBA have good solubility in pentaerythritol triacrylate. For comparison, 0.9 g of praseodymium acetate and 2.1 g of pentaerythritol triacrylate were mixed to obtain a mixed solution denoted as Pr-PETA. Fig.21 As shown, praseodymium acetate has low solubility in pentaerythritol triacrylate.

[0115] The particle size distribution of the mixed solution Pr-VBA-PETA obtained by dynamic light scattering is as follows Figure 6 As shown, its particle size is mainly concentrated in the range of 1.0nm-2.0nm. Figure 2 and Figure 6 It can be seen that the praseodymium-based liquid nanoparticles Pr-VBA still maintain a very small particle size after being mixed with pentaerythritol triacrylate.

[0116] Example 4-2:

[0117] Example 4: 0.9 g of praseodymium-based liquid nanoparticles Pr-VBA, 2.1 g of pentaerythritol triacrylate and 0.03 g of I3E photoinitiator were mixed and stirred for 4 hours and used as a photoresist composition for two-photon patterning, and the obtained pattern structure was of high quality.

[0118] Embodiment 5:

[0119] Take 1g of holmium acetate and dissolve it in 4mL of ethyl acetate. Slowly add 4mL of ethyl acetate mixed solution of 1.12g of vinylbenzoic acid and 0.4g of diethylamine under nitrogen protection, and stir at 65°C for 24 hours to obtain a clear solution. After filtering the solution through a 0.22um needle filter, vacuum rotary evaporation is performed at 30°C to obtain holmium-vinylbenzoic acid (referred to as Ho-VBA) nanoparticles.

[0120] The appearance of the holmium-based nanoparticles Ho-VBA is shown in the attached Figure 1 As shown, it is in liquid form.

[0121] The particle size distribution of the holmium-based liquid nanoparticles Ho-VBA obtained by dynamic light scattering is as follows Figure 2 As shown, the particle size is mainly concentrated in the range of 1.0nm-2.0nm.

[0122] The holmium-based liquid nanoparticle Ho-VBA is liquid at room temperature.

[0123] Example 5-1:

[0124] 0.9 g of the holmium-based liquid nanoparticles Ho-VBA prepared in Example 4 and 2.1 g of pentaerythritol triacrylate were mixed and stirred to obtain a mixed liquid referred to as Ho-VBA-PETA.

[0125] The appearance of the mixed solution Ho-VBA-PETA is as follows Fig. 22 As shown, the solubility of holmium-based liquid nanoparticles Ho-VBA in pentaerythritol triacrylate is very good. For comparison, 0.9 g of holmium acetate and 2.1 g of pentaerythritol triacrylate were mixed, and the resulting mixed solution was recorded as Ho-PETA. Fig.23 As shown, it is shown that the solubility of holmium acetate in pentaerythritol triacrylate is low.

[0126] The particle size distribution of the mixed solution Ho-VBA-PETA obtained by dynamic light scattering is as follows Figure 6 As shown, its particle size is mainly concentrated in the range of 1.0nm-2.0nm. Figure 2 and Figure 6 , it can be seen that the holmium-based liquid nanoparticles Nd-VBA still maintain a very small particle size after being mixed with pentaerythritol triacrylate.

[0127] Example 5-2:

[0128] 0.9 g of the praseodymium-based liquid nanoparticles Ho-VBA, 2.1 g of pentaerythritol triacrylate and 0.03 g of I3E photoinitiator prepared in Example 5 were mixed and stirred for 4 hours and used as a photoresist composition for two-photon patterning, and the obtained pattern structure was of high quality.

[0129] Embodiment 6:

[0130] Take 1g of thulium acetate and dissolve it in 4mL of ethyl acetate. Slowly add 4mL of ethyl acetate mixed solution of 1.12g of vinyl benzoic acid and 0.4g of diethylamine under nitrogen protection, and stir at 65°C for 24 hours to obtain a clear solution. After filtering the solution through a 0.22um needle filter, vacuum rotary evaporation is performed at 30°C to obtain thulium-vinyl benzoic acid (referred to as Tm-VBA) nanoparticles.

[0131] The appearance of the thulium-based nanoparticles Tm-VBA is shown in the attached Figure 1 As shown, it is in liquid form.

[0132] The particle size distribution of the thulium-based liquid nanoparticles Tm-VBA obtained by dynamic light scattering is as follows Figure 2 As shown, the particle size is mainly concentrated in the range of 1.0nm-2.0nm.

[0133] The thulium-based liquid nanoparticles Tm-VBA are liquid at room temperature.

[0134] Example 6-1:

[0135] 0.9 g of the thulium-based liquid nanoparticles Tm-VBA prepared in Example 4 and 2.1 g of pentaerythritol triacrylate were mixed and stirred to obtain a mixed solution referred to as Tm-VBA-PETA.

[0136] The appearance of the mixed solution Tm-VBA-PETA is as follows Fig.24 As shown, the solubility of thulium-based liquid nanoparticles Tm-VBA in pentaerythritol triacrylate is very good. For comparison, 0.9 g of thulium acetate and 2.1 g of pentaerythritol triacrylate were mixed, and the resulting mixed solution was recorded as Tm-PETA. Fig.25 As shown, it is shown that the solubility of thulium acetate in pentaerythritol triacrylate is low.

[0137] The particle size distribution of the mixed solution Tm-VBA-PETA obtained by dynamic light scattering is as follows Figure 6 As shown, its particle size is mainly concentrated in the range of 1.0nm-2.0nm. Figure 2 and Figure 6 It can be seen that the thulium-based liquid nanoparticles Tm-VBA still maintain a very small particle size after mixing with pentaerythritol triacrylate.

[0138] Example 6-2:

[0139] 0.9 g of the praseodymium-based liquid nanoparticles Tm-VBA prepared in Example 6, 2.1 g of pentaerythritol triacrylate and 0.03 g of I3E photoinitiator were mixed and stirred for 4 hours and used as a photoresist composition for two-photon patterning, and the obtained pattern structure was of high quality.

[0140] Embodiment 7:

[0141] 1 g of ytterbium acetate was dissolved in 4 mL of ethyl acetate, and 4 mL of a mixed solution of 1.12 g of vinyl benzoic acid and 0.4 g of diethylamine in ethyl acetate was slowly added dropwise under nitrogen protection, and stirred at 65°C for 24 hours to obtain a clear solution. The solution was filtered through a 0.22 um needle filter and vacuum evaporated at 30°C to obtain ytterbium-vinyl benzoic acid (denoted as Yb-VBA) nanoparticles.

[0142] The appearance of the ytterbium-based nanoparticles Yb-VBA is shown in the attached Figure 1 As shown, it is in liquid form.

[0143] The particle size distribution of the ytterbium-based liquid nanoparticles Yb-VBA obtained by dynamic light scattering is as follows Figure 2 As shown, the particle size is mainly concentrated in the range of 1.0nm-2.0nm.

[0144] The ytterbium-based liquid nanoparticle Yb-VBA is liquid at room temperature.

[0145] Example 7-1:

[0146] 0.9 g of the ytterbium-based liquid nanoparticles Yb-VBA prepared in Example 7 and 2.1 g of pentaerythritol triacrylate were mixed and stirred to obtain a mixed liquid referred to as Yb-VBA-PETA.

[0147] The appearance of the mixed solution Yb-VBA-PETA is as follows Fig.26 As shown, the solubility of ytterbium-based liquid nanoparticles Yb-VBA in pentaerythritol triacrylate is very good. For comparison, 0.9 g of ytterbium acetate and 2.1 g of pentaerythritol triacrylate are mixed, and the resulting mixed solution is recorded as Yb-PETA. Fig. 27 As shown, it is shown that ytterbium acetate has low solubility in pentaerythritol triacrylate.

[0148] The particle size distribution of the mixed solution Yb-VBA-PETA obtained by dynamic light scattering is as follows Figure 6 As shown, its particle size is mainly concentrated in the range of 1.0nm-2.0nm. Figure 2 and Figure 6 It can be seen that the ytterbium-based liquid nanoparticles Yb-VBA still maintain a very small particle size after mixing with pentaerythritol triacrylate.

[0149] Example 7-2:

[0150] 0.9 g of the praseodymium-based liquid nanoparticles Yb-VBA prepared in Example 7, 2.1 g of pentaerythritol triacrylate and 0.03 g of I3E photoinitiator were mixed and stirred for 4 hours and used as a photoresist composition for two-photon patterning, and the obtained pattern structure was of high quality.

[0151] The above-described embodiments provide a detailed description of the technical solutions of the present invention. It should be understood that the above descriptions are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing rare earth element-based liquid nanoparticles, characterized in that: The steps include: Rare earth metal acetate is dissolved in an organic dispersion solvent, and an organic acid ligand and an organic amine ligand are dropped under the protection of nitrogen or an inert gas to react to obtain liquid nanoparticles dissolved in the organic dispersion solvent, and the organic dispersion solvent is heated and evaporated to obtain rare earth element-based liquid nanoparticles.

2. The preparation method according to claim 1, characterized in that: If there is precipitation in the reaction system after the reaction, centrifugation is first performed, and after centrifugation, the upper clear solution is taken, and the organic dispersing solvent therein is heated and evaporated to obtain rare earth element-based liquid nanoparticles; Preferably, the solution after the reaction is first filtered, and then heated to evaporate the organic dispersing solvent therein; Preferably, filtering is performed through a filter with a pore size of 0.1 um-0.5 um.

3. The preparation method according to claim 1, characterized in that: The particle size of the rare earth element-based liquid nanoparticles is in the range of 0.8nm-8nm, preferably in the range of 1nm-2nm.

4. The preparation method according to claim 1, characterized in that: The organic acid ligand and the organic amine ligand are dispersed in the organic dispersion solvent to obtain a dispersion solution; the rare earth metal acetate is dissolved in the organic dispersion solvent and dripped into the dispersion solution under nitrogen protection.

5. The preparation method according to claim 1, characterized in that: The rare earth metal acetate is selected from one or more of erbium acetate, ytterbium acetate, praseodymium acetate, neodymium acetate, yttrium acetate, thulium acetate, holmium acetate, samarium acetate, and cerium acetate; Preferably, the organic dispersing solvent is selected from one or more of ethyl acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, methanol, ethanol and propanol.

6. The preparation method according to claim 1, characterized in that: The organic acid ligand is selected from aromatic carboxylic acids, and its general formula is HOOC-R1-C6H4-R2, Wherein, R1 is selected from C0-C3 alkyl, and R2 is selected from one or more of halogen, carboxyl, carbonyl, hydroxyl, amino, C1-C10 alkyl, C2-C10 alkenyl, C3-C10 aryl, benzophenone derivatives, and thioxanthone derivatives.

7. The preparation method according to claim 1, characterized in that: The organic amine ligand is selected from chain amine and its derivatives or cyclic amine and its derivatives; The chain amine and its derivatives are selected from one or more of trimethylamine, triethylamine, tripropylamine, tripentylamine, triisopropylamine, diethylamine and dimethylamine; The cyclic amine and its derivatives are selected from but not limited to one or more of imidazole and its derivatives, pyridine and its derivatives, piperidine and its derivatives, pyrimidine and its derivatives, pyrrole and its derivatives.

8. The preparation method according to claim 1, characterized in that: The molar mass ratio of the rare earth metal acetate, the organic acid ligand and the organic amine ligand is selected from 1: (0.5-3): (0.5-3); Preferably, the reaction is carried out at 60°C-80°C.

9. A photoresist composition, characterized in that: The invention comprises an organic resin, a photoinitiator and rare earth element-based liquid nanoparticles obtained by the preparation method described in any one of claims 1 to 10, wherein the rare earth element-based liquid nanoparticles are uniformly dispersed in the organic resin.

10. The photoresist composition according to claim 9, characterized in that: The organic resin is selected from acrylates and their derivatives; Preferably, the acrylate and its derivatives are selected from one or more of pentaerythritol tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, polydipentaerythritol pentaacrylate, and 3-(trimethoxysilyl)propyl methacrylate.

11. The photoresist composition according to claim 9, characterized in that: The mass ratio of the rare earth element-based liquid nanoparticles to the organic resin is (0.1-1):1; Preferably, the photoinitiator is selected from one or more of 2-isopropylthioxanthone, benzophenone, 2,4-diethylthioxanthone, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone; Preferably, the mass of the photoinitiator accounts for 0-5% of the mass of the photoresist composition.

12. A 3D pattern, characterized by: Placing the photoresist composition of claim 9, 10 or 11 on the surface of a substrate, patterning the substrate by two-photon polymerization femtosecond laser direct writing, taking out the substrate and immersing it in a developer for development, and drying it to obtain the pattern; Preferably, the photoresist composition is placed on the substrate surface by dripping, casting or coating; Preferably, the substrate is selected from a polished silicon wafer, a quartz wafer or a sapphire wafer; Preferably, the developer is selected from one or more of isopropyl alcohol, toluene, o-xylene, 4-methyl-2-pentanol, propylene glycol monomethyl ether acetate, and ethyl acetate.